Increased growing temperature reduces content of polyunsaturated fatty acids in four oilseed crops - Schulte, Leslie R.; Ballard, T.; Samarakoon, Thilani Nishanthika; Yao, Libin; Vadlani, Praveen V.; Staggenborg, Scott A.; Rezac, Mary E. (My University, 2014)
Environmental temperature directly influences the lipid profile produced by oilseeds. If growing temperatures increase, as is predicted by current models, the precise profile of lipids produced are likely to change. This paper develops models to predict lipid profiles as a function of growing temperature. Data relating to lipid profiles of soybean (Glycine max), spring canola (Brassica napus), spring camelina (Camelina sativa), and sunflower (Helianthus annuus) were gathered from the literature and evaluated to examine the influence of temperature on relative production of oleic, linoleic, and linolenic acid. For each crop, a set of linear regressions was used to correlate temperature during the grain fill, defined as 30 days before harvest, with the molar percentages of oleic, linoleic, and linolenic acid present. An increase in temperature from 10 to 40°C resulted in an increase in the production of oleic acid and a decrease in the production of linoleic and linolenic acid in soybeans, canola, and sunflowers. Over the range of data available, the lipid profile of camelina was temperature insensitive. To test the validity of the correlations, the four crops were grown in a field study in Manhattan, Kansas simultaneously, in the same environment, in 2011. The correlations accurately predicted the field data for soybean, canola, and camelina but not for sunflower. The correlation for sunflower under-predicted the molar amount of oleic acid and over-predicted the molar amount of linoleic acid. This study indicates increasing growing temperatures from 10 to 40°C will result in more monounsaturated oils and less polyunsaturated oils in soybean, canola, and sunflower.
Keywords: Fatty acid profile; Unsaturated oils; Glycine max; Brassica napus; Camelina sativa; Helianthus annuus